Management of Meloidogyne incognita in yambased cropping systems with cover crops - Claudius-Cole, A.O.; Fawole, B.; Asiedu, Robert; Coyne, Danny L. (Elsevier, 2014)
The effect of intercropping cover crops was with yam was assessed for nematode management both inpot and field conditions in Nigeria. The cover crops were sown with yams in pots containing sterile soiland inoculated with 5000 eggs of Meloidogyne incognita. In the field, each cover crop was separatelyintercropped with yams inoculated with 10,000 nematodes. From both pot and field experiments, nonematode damage was observed on yam tubers that were intercropped with Aeschynomene histrix,Crotolaria juncea, and Tagetes erecta. Damage in intercropped tubers was reduced by 72.7% with Mucunapruriens, Centrosema pubescens, and Pueraria phaseoloides and by 58.3% with Stylosanthes guianensiscompared to yams planted without cover crops; they also had lower (p _ 0.05) nematode populations.Cajanus cajan, Lablab purpureus and Vigna unguiculata however, supported high nematode populationsand led to nematode damage in intercropped yams. Tubers from M. incognita-inoculated plants weremore damaged and lost 42% more weight (p _ 0.05) following three months of storage than tubers fromuninoculated plants. Intercropping yams with selected cover crops can be useful in managingM. incognita without reducing yam yields.